Peran Rahmah El Yunusiyah Dalam Meningkatkan Kualitas Pendidikan Islam Di Sekolah - Salma Navi’ati Kholisa Dewi; Mulyanto Abdullah Khoir; Gali Nurma Saudi; Sabila Nurul Azizah (Al-Abshor : Jurnal Pendidikan Agama Islam, 2024)
This study examines the crucial role of Rahmah El Yunusiyah in improving the quality of Islamic education in schools, emphasizing the contributions of her thought and practice, particularly for women. Rahmah, an educational figure from West Sumatra, is known as a pioneer of modern Islamic education that integrates Islamic values ​​with general knowledge and character building. Through the establishment of Diniyah Puteri Padang Panjang in 1923, she presented an innovative, values-based educational model, while simultaneously positioning women as active subjects in the teaching and learning process. This study uses a descriptive qualitative approach with a literature study method to explore Rahmah's ideas, strategies, and influence on the development of the Islamic education system. The results of the study indicate that Rahmah's thinking is able to encourage educational transformation through the implementation of a holistic curriculum, which not only teaches knowledge and skills but also emphasizes the development of noble morals. She also positions the role of women as educators and prime movers, thus opening up space for women's empowerment in the world of Islamic education. Furthermore, Rahmah El Yunusiyah's ideas are not only relevant in the historical context of her struggle but also serve as a valuable inspiration for the development of contemporary Islamic education. Her thinking provides a foundation for the creation of quality, inclusive, and gender-equitable Islamic education. By emphasizing that education is a means to improve the dignity and worth of women, Rahmah has succeeded in building a legacy that remains relevant today, especially in facing the challenges of globalization and the need for education that is humanistic and oriented towards Islamic values. Abstrak Penelitian ini membahas peran penting Rahmah El Yunusiyah dalam meningkatkan kualitas pendidikan Islam di sekolah, dengan menekankan kontribusi pemikiran dan praksisnya, terutama bagi perempuan. Rahmah, tokoh pendidikan asal Sumatera Barat, dikenal sebagai pelopor pendidikan Islam modern yang mengintegrasikan nilai-nilai keislaman dengan ilmu pengetahuan umum serta pembentukan karakter. Melalui pendirian Diniyah Puteri Padang Panjang pada tahun 1923, ia menghadirkan model pendidikan yang inovatif dan berbasis nilai, sekaligus menempatkan perempuan sebagai subjek aktif dalam proses belajar mengajar. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan metode studi pustaka untuk menelusuri gagasan, strategi, dan pengaruh Rahmah terhadap perkembangan sistem pendidikan Islam. Hasil kajian menunjukkan bahwa pemikiran Rahmah mampu mendorong transformasi pendidikan melalui penerapan kurikulum yang holistik, yang tidak hanya mengajarkan ilmu pengetahuan dan keterampilan, tetapi juga menekankan pembinaan akhlak mulia. Ia juga menempatkan peran perempuan sebagai pendidik dan penggerak utama, sehingga membuka ruang bagi pemberdayaan perempuan dalam dunia pendidikan Islam. Lebih jauh, gagasan Rahmah El Yunusiyah tidak hanya relevan dalam konteks historis masa perjuangannya, tetapi juga menjadi inspirasi berharga dalam pengembangan pendidikan Islam kontemporer. Pemikirannya memberikan landasan bagi terciptanya pendidikan Islam yang bermutu, inklusif, dan berkeadilan gender. Dengan menegaskan bahwa pendidikan adalah sarana untuk meningkatkan harkat dan martabat perempuan, Rahmah berhasil membangun warisan yang tetap aktual hingga kini, terutama dalam menghadapi tantangan globalisasi dan kebutuhan akan pendidikan yang humanis serta berorientasi pada nilai-nilai keislaman.